1997
DOI: 10.1074/jbc.272.28.17873
|View full text |Cite
|
Sign up to set email alerts
|

Protein Phosphatase 2C Acts Independently of Stress-activated Kinase Cascade to Regulate the Stress Response in Fission Yeast

Abstract: Stress-activated signal transduction pathways, which are largely conserved among a broad spectrum of eukaryotic species, have a crucial role in the survival of many forms of stress. It is therefore important to discover how these pathways are both positively and negatively regulated. Recent genetic studies have implicated protein phosphatase 2C (PP2C) as a novel negative regulator of stress response pathways in both budding and fission yeasts. Moreover, it was hypothesized that PP2C dephosphorylates one or mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
67
2
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 29 publications
7
67
2
1
Order By: Relevance
“…We conclude that signals from Spc1 kinase that are required for G 0 arrest are not transduced exclusively via Atf1-Pcr1-M26 complex acting on the cgs2 ϩ promoter. This finding is consistent with, and provides an explanation for, previous findings: First, some Spc1-dependent stress responses do not require Atf1 and Pcr1 (13,36,(41)(42)(43)(44)(45). Second, recent transcriptional profiling revealed that only about one quarter of the Spc1-dependent genes are dependent upon Atf1 (dependence upon Pcr1 was not tested) (46).…”
Section: Atf1-pcr1-m26 Complex At Cgs2supporting
confidence: 79%
“…We conclude that signals from Spc1 kinase that are required for G 0 arrest are not transduced exclusively via Atf1-Pcr1-M26 complex acting on the cgs2 ϩ promoter. This finding is consistent with, and provides an explanation for, previous findings: First, some Spc1-dependent stress responses do not require Atf1 and Pcr1 (13,36,(41)(42)(43)(44)(45). Second, recent transcriptional profiling revealed that only about one quarter of the Spc1-dependent genes are dependent upon Atf1 (dependence upon Pcr1 was not tested) (46).…”
Section: Atf1-pcr1-m26 Complex At Cgs2supporting
confidence: 79%
“…Recently, two groups showed that steady laminar flow stimulated c-Jun NH 2 -terminal kinases (JNK1 and JNK2) to a greater extent than extracellular signalregulated kinase (ERK)1͞2 (12,14). However, these results are inconsistent with the concept that flow promotes atheroprotective events because JNK activity is stimulated by inflammatory cytokines (15,16), which are thought to promote atherosclerosis (17). We believe that more appropriate experimental conditions to investigate the effects of flow on JNK activity would be in the presence of cytokine stimulation.…”
contrasting
confidence: 54%
“…In fission yeast cells, the expression of Ptc1 is enhanced by hyperosmotic stress (29). In contrast, expression levels of PP2C␣ and PP2C␤-1 are not altered following stress treatment of cells (17).…”
Section: Pp2c␤mentioning
confidence: 93%